“Laic State is not Atheistic state”: Some reflections about Religion, State and Education from the “law of the bible” in Florianópolis/SC - Oliveira, Amurabi (2017)
The present work aims to discuss the relationship between State and Religion in Brazil, taking as a guideline the discussion about the approval of Law nº 9.374 of march 11, 2015, which instituted the obligatory of the presence of the bible in schools in Florianópolis/SC, the law was elaborated by the councilman Jerônimo Alves (PRB), also known as Bishop Jerônimo Alves. I am interested here to understand the dispute over the concept of secularism, in which certain groups begin to seek to include their demands in the political agenda, so that, in my understanding, they do not seek with theses actions that they articulate, that passes through bills of laws like this, but also the institutionalization of new commemorative dates and the construction of monuments of religious character, but a semantic extension of the concept of laicity, which comes amid a process of Pentecostal expansion which goes beyond the numerical figures referring to those who claimed to be evangelicals, especially pentecostal evangelicals.